Pengetahuan Sikap Dan Tindakan Petani Bawang Merah Dalam Penggunaan Pestisida (Studi Kasus di Kabupaten Nganjuk Propinsi Jawa Timur) - Luluk Sulistiyono; Rudy C. Tarumingkeng; Bunasor Sanim; Dadang Dadang (Agroland: Jurnal Ilmu-ilmu Pertanian, 2008)
The aim of the research was to probe farmer’s knowledge, attitude and action on the use of pesticide and its impact on the health of the farmers and the population of various organisms. The research was conducted in the production center of shallot at Nganjuk regency of East Java Province from March to August 2002 and used the survey method. The number of respondents was 192 farmers selected based on the Stratified Sampling method at six villages from three sub-districts. The results showed that the SLPHT farmers had a high level of attitude and knowledge on the use of pesticide whereas the non-SLPHT farmers only had low to moderate level of both. However, the farmer’s attitude and knowledge were not implemented when they applied the pesticide on their crop. Harmful effects of the pesticide misuse have degraded the farmer health with symptoms such as unconscious, blindness and also acetilcollin enzyme disorder. The population of local organisms was also reduced. In conclusion, the farmers had overlooked their own knowledge and attitude when pesticides were applied in the field, consequently the farmers’ health were at risk.